(untitled) (Revista Logos Ciencia & Tecnología, 2019)
This article presents an approximation to the characterization of the strategic student profile for the Differential Calculus course. According to the problem and the objectives that were proposed, an investigation with descriptive exploratory scope was considered, with a non-experimental type design. The results of this research helped to propose, for the future, the development of other studies linked to the implementation of the proposal of the pedagogical and didactic model mediated by information and communication technologies (ICT) that allow for the promotion of the dynamic role of the student in his/her learning process, as well as a new configuration of the teaching role from the pedagogical posture framed in teaching and strategic learning.